Beyond Pain Relief: A Review on Cannabidiol Potential in Medical Therapies - Mariana Luz-Veiga; João Azevedo-Silva; João C. Fernandes (MDPI AG, 2023)
The phytocannabinoid cannabidiol (CBD) is receiving increasing attention due to its pharmacological properties. Although CBD is extracted from Cannabis sativa, it lacks the psychoactive effects of Δ9-tetrahydrocannabinol (THC) and has become an attractive compound for pharmacological uses due to its anti-inflammatory, antioxidant, anticonvulsant, and anxiolytic potential. The molecular mechanisms involved in CBD's biological effects are not limited to its interaction with classical cannabinoid receptors, exerting anti-inflammatory or pain-relief effects. Several pieces of evidence demonstrate that CBD interacts with other receptors and cellular signaling cascades, which further support CBD's therapeutic potential beyond pain management. In this review, we take a closer look at the molecular mechanisms of CBD and its potential therapeutic application in the context of cancer, neurodegeneration, and autoimmune diseases.